Identification of PsbS binding proteins in Arabidopsis thaliana leaf chloroplasts under high light using TurboID-based proximity labeling - Jiao, Yuwei; Dou, Yanhui; Wang, Lihua; Zhu, Xin-Guang; Zheng, Huiqiong (Frontiers in Plant Science, 2026)
Photosystem II Subunit S (PsbS) is a critical regulator of non-photochemical quenching (NPQ), which is a protective mechanism triggered to dissipate excess light energy as heat and prevent photodamage. However, the molecular basis of how PsbS interact with partner proteins to regulate NPQ remains unclear. In this study, we employed proximity labeling to identify PsbS interaction proteins in situ in living cells of Arabidopsis leaves via biotinylation during NPQ. Arabidopsis plants stably expressing PsbS constructs fused to proximity labeling enzyme TurboID were generated and the biotinylated proteomes were analyzed by liquid chromatography-mass spectrometry. The interactomes of PsbS under dark and under light were generated, which not only confirmed several known PsbS-interacting proteins, such as Lhcb1.3, Lhcb3, and Lhcb4.2, but also identified many novel binding proteins. Interestingly, most of these protein interactions of PsbS were unaffected by light, which suggest that PsbS might influence the NPQ through conformational changes without a large physical migration within thylakoid membrane. Analyses of the interactomes also show a few proteins enhanced (such as TLP18.3) or some proteins inhibited (such as ZEP) under the high light, suggesting that the NPQ and repair process after photoinhibition might be coordinated.